Empathy-Based Character Education in Religious Education Contexts: A Systematic Review of the Literature - Heny Susilawati; D.Y.P. Sugiharto; Sunawan Sunawan; Heru Mugiarso (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The purpose of this study is to conduct a systematic review of the literature for the last 5 years (2019–2024) related to the use of empathy-based approaches for character education in faith-based organizations. The method used is a Systematic Literature Review (SLR) approach, following the PRISMA 2020 guidelines, consisting of four primary stages: identification, screening, eligibility screening, and synthesis of the final 14 selected studies per the inclusion criteria. The review concludes by identifying four main themes: (1) models and practices of empathy-driven character education; (2) spiritual and affective values’ incorporation; (3) challenges and barriers to implementation; and (4) an empirical understanding of whether empathy contributes to forming holistic religious character. The results suggest that empathy can be enhanced through pedagogical techniques including religious telling, interfaith dialogue, service learning, and spiritual reflection. However, barriers such as lack of teacher training, resistance from the system and inconsistency of values still present major challenges. The study suggests a shift in pedagogic and policy focus to the nurturing of empathy in religious education systems. Its theoretical and practical contributions should further inform thinking about 21st-century character education as more human centred, reflective and situated. Introduction Character education is now perhaps more vital than ever before to schools but its definition and implementation is still open to interpretation and debate